The big book of monsters : the creepiest creatures from classic literature - Johnson, Hal, 1972- (Workman Publishing, 2019)
Provides illustrated profiles of twenty-five monsters from classic literature including Dracula, Frankenstein's Monster, and the Jabberwocky. Contains sidebars about the monsters' literary origins, authors, genres, fear factors, and powers.